2007
DOI: 10.1016/j.ces.2007.05.030
|View full text |Cite
|
Sign up to set email alerts
|

On the numerical study of isothermal vertical bubbly flow using two population balance approaches

Abstract: Two population balance approaches based on the MUltiple-SIze-Group (MUSIG) model and one-group Average Bubble Number Density (ABND) model for handling the bubble size distribution of gas-liquid bubbly flows under isothermal conditions are assessed. Three forms of coalescence and breakage mechanisms by Wu et al. (1998), Hibiki and Ishii (2002) and Yao and Morel (2004) are incorporated in the ABND model. To examine the relative merits of both approaches, local radial distributions of five primitive variables in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(62 citation statements)
references
References 47 publications
4
54
0
1
Order By: Relevance
“…Figures 3 and 4 show that the simulation results are in quite good agreement with the experimental data. In [31], computations performed with a K-ε turbulence model for the liquid produced comparable results. Our main objective in this paper is to check that the simulation with the R i j -ε turbulence model gives satisfactory results in a simple geometry, which is crucial before calculating industrial geometries, where the K-ε turbulence model is susceptible to fail.…”
Section: The Liuandbankoff Casesupporting
confidence: 50%
See 1 more Smart Citation
“…Figures 3 and 4 show that the simulation results are in quite good agreement with the experimental data. In [31], computations performed with a K-ε turbulence model for the liquid produced comparable results. Our main objective in this paper is to check that the simulation with the R i j -ε turbulence model gives satisfactory results in a simple geometry, which is crucial before calculating industrial geometries, where the K-ε turbulence model is susceptible to fail.…”
Section: The Liuandbankoff Casesupporting
confidence: 50%
“…Other forces, like the turbulent dispersion force, have also a crucial effect on the void fraction distribution. These forces depend on uncontrolled parameters like the bubble shape, the liquid turbulence, the bubbles collective effects, and so on [31]. [32] investigated experimentally several upwards bubbly flows in a vertical pipe with a sudden expansion.…”
Section: The Liuandbankoff Casementioning
confidence: 99%
“…Comparisons between the k-ε model and LES simulations have shown that similar performances are obtained in terms of average quantities; conversely, more accurate fluctuating quantities are achievable through LES [436][437][438][439], owing to the isotropic turbulence hypothesis of the k-ε model. The SST k-ω model has proven to be slightly superior to the k-ε model for simulating upward bubbly flow [440,441] and vertical pipes [10,430,[442][443][444][445][446][447]. It is worth noting that suitable prediction and selection of inlet turbulent boundary conditions are needed for reliable predictions [448].…”
Section: The Eulerian Multi-fluid Approachmentioning
confidence: 99%
“…Rzehak et al [459] compared various formulations applied to vertical bubbly flow in a pipe and concluded that the inclusion of this force into the model is fundamental. The virtual mass force arises from the relative acceleration of an immersed moving object to its surrounding fluid; this force is often found to be negligible in bubble column simulations [421,428,437,439,449,460], and different studies have neglected it [420,430,440,441,446,450,458,[461][462][463][464][465][466][467][468][469]. Recently, Ziegenhein et al [10] demonstrated that the virtual mass force has an influence on the prediction of the turbulence intensity at higher flow rates.…”
Section: The Eulerian Multi-fluid Approachmentioning
confidence: 99%
See 1 more Smart Citation